Perfil de ácidos grasos de un cultivar tetraploide de Lolium multiflorum en dos cortes sucesivos - Montenegro, Luciano Federico; Perez, Carolina Daiana; Garcia, Pilar Tere; Olivera, María Elena; Postulka, Elena B. (Asociación Argentina de Producción Animal, 2022)
The use of fresh pastures for animal feed is advantageous because they are constituting a low-cost food, and have a profile of fatty acids rich in alpha-linolenic acids (18:3 n-3), belonging to the omega 3 family and oleic acid (18:1 n-9) of the omega 9 family. At present, animal production sciences are pursuing the production of products of animal origin rich in omega 3 fatty acids, low in omega 6 and with a low omega 6/omega 3 ratio. This can be achieved by feeding the animals. One of the most used temperate forage species is Lolium multiflorum Lam. This forage has a high endowment of valuable fatty acids, however, they present variation throughout the growth cycle, which affects the concentration of said compounds throughout the growth cycle different courts. The objective of this trial was to determine the variation in the fatty acid profile in two successive cuts of a tetraploid cultivar of Lolium multiflorum Lam (annual ray gras). From the results obtained in this trial, it is concluded that the tetraploid cultivar Bill Max of Lolium multiflorum Lam, presents a profile of fatty acids rich in alpha-linolenic and oleic acid, healthy for the animal feed in addition to an adequate omega 6/omega 3 ratio. On the other hand, the concentration of said Fatty acids vary appreciably throughout the growing season. The deepening of these results could serve as a basis for the study and development of techniques for the use of the forage species to take advantage of the cuts higher concentration of valuable fatty acids.